Tantangan modernisasi hukum dalam era kontemporer - Alamsyah, Risky; Firdaus, Muhammad Rizal; Maharani, Rifa Arum Tazkya (Maliki Interdisciplinary Journal, 2025)
Legal modernization is a response to the evolving dynamics of the times, especially in the contemporary era marked by globalization, technological advances, and the transformation of social values. This article discusses the main challenges in Indonesia’s legal modernization process, including overlapping regulations, legal culture resistance, and weak law enforcement. Through a descriptive qualitative approach and literature analysis, this article highlights the need for legal reform that focuses not only on substance reform, but also on establishing a legal system that is adaptive, participatory, and responsive to the needs of society. It also emphasizes the importance of synergy between policymakers, academics, and civil society to create an inclusive and equitable legal system. Thus, legal modernization in the contemporary era is an important foundation in building a progressive and contextual rule of law.